1934
DOI: 10.1084/jem.59.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Blood Plasma Protein Given by Vein Utilized in Body Metabolism

Abstract: Large amounts of normal blood plasma can be given intravenously to normal dogs over several weeks without causing any significant escape by way of the urine. There appears to be no renal threshold for plasma protein even with high plasma protein concentration (9.7 per cent). Dogs receiving sugar by mouth and plasma by vein can be kept practically in nitrogen equilibrium and it would seem that the injected protein must be utilized by the body. If this can happen in this emergency we may suspect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1935
1935
1950
1950

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…Nevertheless, it is difficult to reconcile this view with other known facts. It has already been shown that different kinds of food protein cause different rates of regeneration in the dog (10,20). The evidence submitted here appears to point quite definitely to an increased rate of formation of serum protein in the periods in which the intake of protein was increased, but with respect to the animal proteins tested, quantity seems to have been fully as important a factor as quality in increasing proteinuria.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Nevertheless, it is difficult to reconcile this view with other known facts. It has already been shown that different kinds of food protein cause different rates of regeneration in the dog (10,20). The evidence submitted here appears to point quite definitely to an increased rate of formation of serum protein in the periods in which the intake of protein was increased, but with respect to the animal proteins tested, quantity seems to have been fully as important a factor as quality in increasing proteinuria.…”
Section: Discussionmentioning
confidence: 46%
“…Little attention has been given to the kind of protein fed and its effect upon hypoproteinemia, proteinuria and the storage of protein in the tissues.2 The problem of hypoproteinemia is of especial interest, since no satisfactory means of increasing the concentration of the serum proteins of the nephritic has been discovered. Recently a systematic attempt has been made by Whipple and collaborators (10,20) to ascertain factors governing the regeneration of plasma proteins. By repeated plasmapheresis of the dog they have shown the existence of a reserve depot containing precursors of the serum proteins.…”
mentioning
confidence: 99%
“…It is felt by some investigators (7,8) that the positive balance obtained is an illusory affair and that the actual utilization is poor in some instances. On the other hand, Whipple and coworkers (9) believe that parenteral plasma protein can supply all the requirements for maintenance over a considerable period of time. This implies that there is an exchange between the tissues and the injected protein and that this exchange satisfies the need of endogenous metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In 1934 Whipple et al (1) suggested that protein stores existed in body tissues and postulated that a "dynamic equilibrium" between plasma proteins and these tissue stores was an integral part of protein metabolism. This concept has gradually been accepted by most investigators in the field of nutrition (24).…”
mentioning
confidence: 99%
“…Ravdin (8) has stated, "If the means to determine it were available, the first effect of protein undernutrition is a reduction in the amount of protein stores in the tissues of the body since every attempt is made to maintain the serum protein concentration at a nearly normal level." Localio et al (9) in an attempt accurately to evaluate protein reserves, determined the nitrogen 1 content of the rectus abdominis fascia, at the time of surgery, in patients suspected of having a protein deficiency and in patients who were considered to be in a state of normal nutrition. This method of evaluating tissue proteins is of no value before surgery and, in addition, is arduous and time consuming.…”
mentioning
confidence: 99%